FGFR3 Alterations in the Era of Immunotherapy for Urothelial Bladder Cancer - Kacew, Alec; Sweis, Randy F. (Frontiers in Immunology, 2020)
FGFR3 is a prognostic and predictive marker and is a validated therapeutic target in urothelial bladder cancer. Its utility as a marker and target in the context of immunotherapy is incompletely understood. We review the role of FGFR3 in bladder cancer and discuss preclinical and clinical clues of its effectiveness as a patient selection factor and therapeutic target in the era of immunotherapy.